Enforcement of Intellectual Property Law in Indonesia - Nainggolan, Bernard (UNISSULA, 2022)
Intellectual Property Rights (IPR) play a crucial role in the creative economy, and the state must provide legal protection for intellectual property as a form of appreciation for creators/inventors for their efforts and hard work in producing new innovations, while minimizing intellectual property infringements. In practice, there are several challenges and difficulties in enforcing laws related to Intellectual Property Rights (IPR). This research aims to explore the role of IPR in supporting the development of the creative economy in Indonesia. The research method applied is the normative legal research method. This approach explores information from written regulations and legal literature related to IPR in Indonesia. The data used is secondary data obtained through literature studies. The conclusion of this research indicates that IPR protection plays a central role in supporting the ecosystem of the creative economy. However, challenges such as the lack of awareness among the public and creators about the importance of protecting intellectual property, as well as deficiencies in regulations supporting the protection of traditional knowledge, need to be addressed. Collaborative efforts between the government, creative industry stakeholders, and the public are necessary to ensure optimal enforcement of IPR and promote sustainable growth in Indonesia's creative economy.